Beneficial Effects of Poplar Buds on Hyperglycemia, Dyslipidemia, Oxidative Stress, and Inflammation in Streptozotocin-Induced Type-2 Diabetes - Shiqin Peng; Ping Wei; Qun Lu; Rui Liu; Yue Ding; Jiuliang Zhang (Journal of Immunology Research)
The effects of propolis on blood glucose regulation and the alleviation of various complications caused by diabetes have been widely studied. The main source of propolis in the northern temperate zone is poplar buds. However, there is limited research on the antidiabetic activity of poplar buds. In order to evaluate the effect of poplar buds on type-2 diabetes, crude extract and 50% fraction of poplar buds were used to feed streptozotocin-induced type-2 diabetic mice. The results showed that 50% fraction could increase insulin sensitivity and reduce insulin resistance, as well as decrease the levels of fasting blood glucose, glycated hemoglobin, and glycosylated serum proteins in diabetic mice. Compared with the model control group, the 50% fraction-treated group showed significant decreases of malondialdehyde (MDA) and increases of superoxide dismutase (SOD) in serum and liver homogenate. Moreover, 50% fraction could significantly decrease total cholesterol (TC), alleviate abnormal lipid metabolism, and enhance antioxidant capacity in the serum. For inflammatory factors, feeding of 50% fraction could also reduce the levels of interleukin 6 (IL-6), tumor necrosis factor α (TNF-α), monocyte chemotactic protein 1 (MCP-1), and cyclooxygenase-2 (COX-2) in liver homogenate. Taken together, our results suggest that crude extract and 50% fraction of poplar buds, particularly the latter, can decrease blood glucose levels and insulin resistance, and 50% fraction can significantly relieve dyslipidemia, oxidative stress, and inflammation caused by type-2 diabetes.